Differentiation Between Early and Severe Stages of Dementia in Claims Data Based on Diagnosis, Prescription, and Utilization Patterns - Moritz Platen; Maresa Buchholz; Anika Rädke; Eva Gläser; Audrey Iskandar; Neeltje van den Berg; Wolfgang Hoffmann; Bernhard Michalowsky (Neurology and Therapy)
Abstract Introduction Claims data typically lack clinical parameters such as dementia severity, limiting insights into disease progression and related healthcare utilization and costs. Although diagnoses, prescriptions, and utilization patterns may serve as proxies, their validity is unclear. This study aimed to identify and validate these parameters to distinguish early from severe dementia stages. Methods Baseline data from 737 patients with dementia were analyzed. Dementia severity was assessed using the Mini-Mental State Examination and classified as early (≥ 27), mild (20–26), and moderate to severe (0–19). Healthcare utilization was recorded via structured interviews. Diagnoses, long-term care levels, and prescribed medications were extracted from physicians’ files. Ordinal logistic regression evaluated associations between predictors and severity, with average marginal effects (AME) quantifying impact. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were computed for key predictors. Results Among the sample (56% female patients, mean age 80), 18% were in the early stages, 43% mild, and 39% moderate to severe. Antipsychotic prescriptions (odds ratio (OR) 3.40, 95% confidence interval (CI) 1.94–5.95), antidementia drugs (OR 2.31, 95% CI 1.56–3.40), and higher long-term care levels (OR 5.59, 95% CI 2.23–13.99 for level ≥ 4) were associated with advanced severity. AME analysis revealed that antipsychotic use reduced early-stage probability by 14% and increased severe-stage probability by 21%. Similarly, antidementia drugs lowered early-stage probability by 9% and raised severe-stage probability by 13%. Increasing care levels were associated with a 2–16% decline in early-stage probability and a 3–34% rise in severe-stage probability. The combined model showed high specificity (99.6%) and PPV (84.6%) for severe dementia, but sensitivity and NPV for early stage were low. Conclusion Antidementia drugs, antipsychotics, and long-term care level serve as robust predictors of moderate to severe dementia, whereas early-stage detection remains challenging. Future studies should validate these markers and explore additional predictors to improve early detection in claims data.